Applied numerical analysis - Gerald, Curtis F.; Wheatley, Patrick O. (Reading MA : Addison-Wesley, 1999)
Numerical computing and computers. Solving nonlinear equations. Solving sets of equations. Interpolation and curve fitting. Approximation of functions. Numerical differentiation and numerical integration. Numerical solution of ordinary differential equations...
Keywords: Numerical analysis; Numerical analysis